Self‐assembled amphiphilic poly‐N‐vinylpyrrolidone nanoparticles as carriers for hydrophobic drugs: Stability aspects. Issue 1 (10th August 2017) - Kuskov, Andrey N.; Kulikov, Pavel P.; Goryachaya, Anastasia V.; Tzatzarakis, Manolis N.; Tsatsakis, Aristidis M.; Velonia, Kelly; Shtilman, Mikhail I.
ABSTRACT: Nanoparticles can experience numerous impacts during storage or after intravenous administration resulting in disassembly and/or drug leakage and affecting their efficiency as drug delivery systems. In this study, this crucial issue was addressed by investigating the stability of amphiphilic poly‐ N ‐vinylpyrrolidone derivative nanocarriers in blood serum, against destabilizing agents and during long‐term storage. All amphiphilic poly‐ N ‐vinylpyrrolidone derivative nanoparticles prepared in this study were found to possess sizes less than 150 nm, narrow size distribution, spherical morphology, and a slightly negative surface charge. These nanoparticles could efficiently entrap hydrophobic substances (pyrene and curcumin) while retaining excellent compatibility with red blood cells. Moreover, our studies demonstrate the stability of the nanoparticles during long‐term storage and upon dilution with body liquids enhancing their potential as stable in vivo carriers, which is critically important for intravenous drug delivery applications. All properties were found to strongly depend on the ratio between the hydrophobic and the hydrophilic moiety of the polymers under study. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 45637. Abstract :